2010
DOI: 10.1590/s0102-76382010000400012
|View full text |Cite
|
Sign up to set email alerts
|

Análise do tratamento cirúrgico da raiz da aorta com o tubo valvulado e com a preservação da valva aórtica

Abstract: Análise do tratamento cirúrgico da raiz da aorta com o tubo valvulado e com a preservação da valva aórticaAnalysis of aortic root surgery with composite mechanical aortic valve conduit and valve-sparing reconstruction 7. Faculty Member of Cardiovascular Surgery Discipline at InCor-FMUSP; CEO of InCor-FMUSP Hospital.Work performed at the Heart Institute, School of Medicine, University of Sao Paulo (InCor-FMUSP), Sao Paulo, SP, Brazil. Sixteen percent of patients had Marfan syndrome and 4.3% had bicuspid aortic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…There was no significant difference in the incidence of thromboembolic and infectious complications when a valve prosthesis was used or when the native valve was spared, different from some literature citations and even from results previously observed in the present institution for patients treated at different points in time when there was a higher need for reoperation due to endocarditis of the valved conduit compared to the native valve [ 4 , 12 ] .…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…There was no significant difference in the incidence of thromboembolic and infectious complications when a valve prosthesis was used or when the native valve was spared, different from some literature citations and even from results previously observed in the present institution for patients treated at different points in time when there was a higher need for reoperation due to endocarditis of the valved conduit compared to the native valve [ 4 , 12 ] .…”
Section: Discussioncontrasting
confidence: 95%
“…However, there is a large amount of discussion about which is the best valved conduit (homograft, xenograft, autograft, mechanical valve and prosthetic conduit or bioprosthetic) and the variety of possibilities according to different age groups [ 1 ] . The possibilities for aortic root reconstruction with preservation of the aortic valve, regardless of the degree of aortic regurgitation, has been largely documented albeit with several considerations about its non-applicability to every patient as well as its complexity, making it difficult to be used by all surgeons [ 2 - 4 ] .…”
Section: Introductionmentioning
confidence: 99%
“…They evaluated the hemodynamic performance of an aortic valved conduit made with glutaraldehyde treated bovine pericardium (AVCP) in animals and find that hemodynamic outcomes found are similar to physiological parameters. Dias et al18 analyzed early and late results of aortic root reconstruction with aortic valve sparing operations and the composite mechanical valve conduit replacement. And claim that this has a low early and late mortality, a high survival free of complications and low need for reoperation.…”
Section: Introductionmentioning
confidence: 99%
“…Whenever possible, VSO must be considered and performed, regardless of patient age and aortic disease etiopathogenesis, as the literature has consistently reported that patients who undergo VSO experience fewer complications related to anticoagulation or reoperations because of infection or prosthesis dysfunction than patients who undergo the Bentall procedure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Since VSO is considered the procedure of choice for treating aortic root disease 3,6,7, we recognize the necessity of demonstrating that performance of aortic valve repair (AVR) during VSO does not compromise the longevity of the procedure and does not affect the freedom from reoperation rate during follow-up. Therefore, the aim of this study was to evaluate whether performance of AVR during VSO changed the length of time for which patients are free from aortic valve reoperation.…”
Section: Introductionmentioning
confidence: 99%